2016
DOI: 10.1177/0284185115617351
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3.0 Tesla magnetic resonance hysterosalpingography in the diagnostic work-up of female infertility

Abstract: 3.0T MR hysterosalpingography is a feasible, simple, fast, safe, and well-tolerated examination, which allows evaluation of tubal patency and other pelvic causes of female infertility in a single session, and it may thus represent a "one-stop-shop" solution in female infertility diagnostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…The study was completed in all 40 patients with good patient compliance as against the previous studies conducted by Sadowski et al and Winter et al in which it was abandoned in 1/17 and 4/37 patients, respectively. [57] In our study, 60% of the patients had bilateral patencies and 40% had bilateral blocks which is similar to the study by Cipolla et al [8] in which 65% patients had patent tubes and 35% patients had either unilateral or bilateral blocks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study was completed in all 40 patients with good patient compliance as against the previous studies conducted by Sadowski et al and Winter et al in which it was abandoned in 1/17 and 4/37 patients, respectively. [57] In our study, 60% of the patients had bilateral patencies and 40% had bilateral blocks which is similar to the study by Cipolla et al [8] in which 65% patients had patent tubes and 35% patients had either unilateral or bilateral blocks.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are also supported by the study conducted by Unterwerger et al [6] in which 8 out of the 10 cases showed concordant results in both MR HSG and cHSG. Cipolla et al [8] in 2016 did a study with 116 patients on 3T using time-resolved 3D sequence. The results showed patencies in 65%, unilateral blocks in 25%, and bilateral blocks in 9.8% patients and suggested MR with HSG as a one-stop investigation tool for infertility imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In existing studies, satisfactory visualization of the fallopian tubes could not be acquired by MR-HSG. Most studies take approximately the same scan technique, while the proportion and type of MR-HSG contrast agent varies greatly (2, 5–7, 10–12). Gd-DTPA and iohexol are commonly used contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance HSG (MR-HSG) has the potential to be a first-line choice for assessing female infertility by using a relatively non-invasive approach. Aside from the possibility of evaluating tubal patency, it provides additional information about pelvic pathologies with high resolution (2,5,6). However, there are two limitations of existing MR-HSG studies.…”
mentioning
confidence: 99%
“…Currently, two imaging modalities can accomplish these requirements: virtual HSG performed with the use of computerized tomography (CT-VHSG) and with the use of magnetic resonance imaging (MR-VHSG). Although the cost of HSG is less than CT-VHSG or MR-VHSG, these minimal invasive imaging modalities allow a complete evaluation of the gynecologic system (cervix, uterus, and fallopian tubes) in a single examination (7)(8)(9)(10)(11)(12)(13). They require state-of-the-art technology to achieve insightful information that allows a comprehensive assessment of the female reproductive organs.…”
mentioning
confidence: 99%